Sea Ranching Feasibility of the Hatchery-Reared Tropical Sea Cucumber Stichopus monotuberculatus in an Inshore Coral Reef Island Area in South China Sea (Sanya, China) - Xu, Qiang; Wu, Peilin; Huang, Duanjie; Xiao, Yulin; Wang, Xinyuan; Xia, Jingquan; Ma, Wengang; Gao, Fei; Wang, Aimin (Frontiers in Marine Science, 2022)
Sea ranching of tropical edible sea cucumbers is an effective way to relieve the overfishing stress on their natural resources and protect the coral reef ecosystem, yet only a few species have been applied in the sea ranching practice based on hatchery-reared juveniles around the world. In this study, an 8-month (April to December) sea ranching study for hatchery-reared edible sea cucumber Stichopus monotuberculatus juveniles was carried out at a tropical coral reef island area in Sanya, China. Several growth performance indexes and basal nutritional components were monitored. Results revealed that the sea cucumbers had a growth rate of 0.35 0.78 mm day-1 during the experimental period, reaching 15.9 cm long before winter. The weight gain reached 491.13% at the end, and most sea cucumbers were able to grow to the commercial size (over 150 g WW) in the first year of sea ranching. The overall specific growth rate (SGR) and survival rates were 0.73 and 27.5%. Most of the death occurred in the first month after release (25.0%–37.5%), and this is probably due to inadaptation to the sudden change of the environment from the hatchery to the wild, which is proved by the remarkable decrease in nutritional indexes (amino acids, total lipid, and crude protein). Stable isotope and lipid biomarkers revealed that the food source mainly comes from water deposits (with microbes), Sargassum sanyaense seaweed debris, phytoplankton, and coral mucus-derived organics. The study proved the feasibility of the sea ranching of the hatchery-reared S. monotuberculatus juveniles in the tropical coral reef island area. Also, it is highly recommended that appropriate acclimation operation before release should be carried out to improve the survival rate of this species.